2018
DOI: 10.3390/pharmaceutics10020046
|View full text |Cite
|
Sign up to set email alerts
|

Acyclovir-Loaded Chitosan Nanospheres from Nano-Emulsion Templating for the Topical Treatment of Herpesviruses Infections

Abstract: Acyclovir is not a good candidate for passive permeation since its polarity and solubility limit is partitioning into the stratum corneum. This work aims to develop a new topical formulation for the acyclovir delivery. New chitosan nanospheres (NS) were prepared by a modified nano-emulsion template method. Chitosan NS were characterized by Dynamic Light Scattering (DLS), Transmission Electron Microscopy (TEM), and an in vitro release study. The in vitro skin permeation experiment was carried out using Franz ce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
50
0
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 73 publications
(51 citation statements)
references
References 27 publications
0
50
0
1
Order By: Relevance
“…NE with particles size around 200 nm showed higher ability to overcome the porcine skin barrier than free drug, assessed by in vitro permeation test. The enhanced anti-herpes zoster activity was noticed, with higher HSV-1 and HSV-2 infected cells uptake than control, confirmed by confocal laser scanning microscopy [ 75 ]. On the other hand, the hepatitis C virus (HCV) is an important RNA virus that affects the human's life quality.…”
Section: Nanostructured Drug-delivery Systemsmentioning
confidence: 93%
“…NE with particles size around 200 nm showed higher ability to overcome the porcine skin barrier than free drug, assessed by in vitro permeation test. The enhanced anti-herpes zoster activity was noticed, with higher HSV-1 and HSV-2 infected cells uptake than control, confirmed by confocal laser scanning microscopy [ 75 ]. On the other hand, the hepatitis C virus (HCV) is an important RNA virus that affects the human's life quality.…”
Section: Nanostructured Drug-delivery Systemsmentioning
confidence: 93%
“…Chitosan nanospheres loaded with acyclovir were synthesized using modified nanoemulsion template method for topical treatment of herpes. The spheres were of the average size of 200 nm and showed better permeation in in vitro skin permeation studies and higher potency against HSV-1 and HSV-2 than the free acyclovir itself [145].…”
Section: Nanospheresmentioning
confidence: 99%
“…Donalisio et al [155] have reported the preparation by a modified nano-emulsion method of chitosan nanospheres (NS) loaded with 8.5% ACV as a topical formulation against both HSV-1 and HSV-2 herpes virus strains. The main component, chitosan, a natural polycationic polysaccharide, was selected as a material for ACV release, due to its distinctive properties: hydrophilic character, in situ gelling, mucoadhesion, permeation enhancing, in addition to a low cytotoxicity, biocompatibility and bioresorbability features [165].…”
Section: Nano-based Antiviral Agents Against Herpes Virusesmentioning
confidence: 99%